Replication Data for Facebook users’ engagement with dental caries misinformation in Brazilian Portuguese - Remiro, Mariana (2024)
The data provided refers to the following information about the publications selected for the study: total interactions, overperforming, and days since the post was made (at the time of analysis). The file also presents the content analysis conducted manually by two previously trained and calibrated evaluators, following a consensus. The content analysis should be interpreted as follows in the README file.